Sistem Pendukung Keputusan Pemilihan Kepala Desa Terbaik Di Kecamatan Batang Kuis Menggunakan Metode MOORA - Samuel Sihombing; Pristiwanto Pristiwanto; A.M Hatuaon Sihite (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Batang Kuis Subdistrict has a list of village heads who serve as village heads, based on the list of village heads in Batang Kuis District, the best village head election will be carried out. The problem faced in this study is that in choosing the best village head, it only looks at the abilities possessed by the village head, even though there are several criteria that can be considered by the sub-district in choosing the best village head. The criteria used in this study are Performance (C1), Community (C2), Knowledge (C3), Discipline (C4) and Attitude (C5). To overcome the problems encountered, a decision support system is needed. The method used in this study is the MOORA method, this method uses 5 criteria, namely: performance, society, knowledge, discipline and attitude. From the results of the study, the results of the decision with the best alternative were obtained, namely (13) in the name of "H. Kasiman" with the acquisition of 0,378.